2011
DOI: 10.1177/0149206311419663
|View full text |Cite|
|
Sign up to set email alerts
|

High-Performance Work Systems and Job Control

Abstract: This study examines relationships among high-performance work systems (HPWS), job control, employee anxiety, role overload, and turnover intentions. Building on theory that challenges the rhetoric versus reality of HPWS, the authors explore a potential "dark side" of HPWS that suggests that HPWS, which are aimed at creating a competitive advantage for organizations, do so at the expense of workers, thus resulting in negative consequences for individual employees. However, the authors argue that these consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
157
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(201 citation statements)
references
References 91 publications
7
157
0
3
Order By: Relevance
“…Little attention has been paid to the link between HPHRP and work outcomes that undermine employee health and well-being such as stress at work (Jensen et al, 2011). Baptiste (2008) found that HPHRP had a significant positive effect on the well-being of employees in the UK.…”
Section: Job Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Little attention has been paid to the link between HPHRP and work outcomes that undermine employee health and well-being such as stress at work (Jensen et al, 2011). Baptiste (2008) found that HPHRP had a significant positive effect on the well-being of employees in the UK.…”
Section: Job Stressmentioning
confidence: 99%
“…Second, these outcomes are critical for organizations nowadays and have been shown to have significant implications for both employees and organizational performance (Eatough et al, 2011;Khatri et al, 2001;Kim, 2005). Finally, testing the effects of HPHRP on job stress, a well-being variable, and quit intentions, which is the strongest indicator of turnover behaviour, will help evaluate whether HPHRP, which are aimed at providing organizations with a competitive advantage, do so at the expense of employees by resulting in negative consequences for workers (Jensen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These innovative practices are referred to as HPWS (Datta et al, 2005;Ferreiraa, Neirab, & Vieirac, 2012;Huselid, 1995;Jensen, Patel, & Messersmith, 2013), dated back to the middle of 80s (Lawler, 1986;Watson, 1985) from American tradition of human resource management which argued that employees contribution is significant to organizational performance (Ferreiraa et al, 2012). Since then HPWS has continued to gain rising support.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ramsay, Scholaris and Harley, 2000;White, Hill, McGovern, Mills, C., and Smeaton, 2003;Jensen, Patel, and Messersmith, 2013;Van De Voorde and Jensen, 2016). These scholars present a "dark side" high performance work practices, arguing that while the implementation of these practices may increase organizational performance, they do so at the cost of making employees work harder and reduce employees" job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…While organizational citizenship behaviors are a positive outcome at the workplace, one could argue that these practices make people work harder and they are expected to put in more than what is required of their job. This could potentially result in negative outcomes for the individual employee in terms of longer working hours that have consequences for their satisfaction at work (White et al, 2003;Jensen et al, 2013;Van De Voorde and Jensen, 2016).…”
Section: Introductionmentioning
confidence: 99%